Strategi Memutus Mata Rantai Pembajakan Hak Cipta pada Seni Batik Nusantara - Hamidulloh Ibda (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2021)
Batik as an artistic and cultural heritage of the archipelago (Nusantara) must be preserved as well as preserved. However, today’s phenomenon is rampant batik piracy. There are three models of batik piracy, namely plagiarism of batik designs, piracy of batik art works, and claims of batik copyright. In 2019 there was copyright on 23 batik motifs owned by the Nabire Regency Government. Not to mention the cases that have not been revealed in the mass media. This article discusses three studies. First, batik as an artistic and cultural heritage of the archipelago. Second, the irony of pirating batik art. Third, the strategy to break the chain of piracy of batik art. Of the strategies examined in this article, there are nine methods of pirating batik. First, assertiveness in taking action against hijackers. Second, protection of local and national batik works. Third, certification and copyright to protect batik from piracy. Fourth, is suing the hijacker legally. Fifth, applying the pillars of art which are not limited to reading, painting, and filing. Sixth, collecting data on batik in Indonesia. Seventh, collective awareness of art, culture, and archipelago heritage inherent in batik. Eighth, in-depth art education through strengthening the curriculum, teachers, subjects, and learning methods. Ninth, it is necessary to have a batik program goes to school or batik goes to campus.